2009
DOI: 10.1007/s00384-009-0679-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of catalytic proteasome subunits in the gut of patients with Crohn’s disease

Abstract: Background and purposeActivation of the transcription factor NF-κB by proteasomes and subsequent nuclear translocation of cytoplasmatic complexes play a crucial role in the intestinal inflammation. Proteasomes have a pivotal function in NF-κB activation by mediating degradation of inhibitory IκB proteins and processing of NF-κB precursor proteins. This study aims to analyze the expression of the human proteasome subunits in colonic tissue of patients with Crohn’s disease.Materials and methodsThirteen patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 31 publications
(34 reference statements)
2
29
0
3
Order By: Relevance
“…Comparable results were obtained from CD patients, who showed high LMP2 and MECL-1 expression in inflamed mucosa (27). Because LMP7 is already expressed in high amounts in healthy control patients, no upregulation of this subunit was observed in CD patients in two additional studies (39,40). Induction of colitis by oral administration of DSS in the drinking water of LMP2-, LMP7-, and MECL-1-deficient mice revealed a nearly complete protection of these mice compared with WT mice (Figs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Comparable results were obtained from CD patients, who showed high LMP2 and MECL-1 expression in inflamed mucosa (27). Because LMP7 is already expressed in high amounts in healthy control patients, no upregulation of this subunit was observed in CD patients in two additional studies (39,40). Induction of colitis by oral administration of DSS in the drinking water of LMP2-, LMP7-, and MECL-1-deficient mice revealed a nearly complete protection of these mice compared with WT mice (Figs.…”
Section: Discussionsupporting
confidence: 60%
“…Administration of a b5-selective inhibitor had no effect on colitis severity. Taken together, these data suggest that, despite the high basal expression of LMP7 in normal colon tissue (39,40), LMP7 represents a targeted approach to the treatment of CD because of the unique role of the immunoproteasome in regulatory inflammatory responses. Our results indicated that LMP7 is directly involved in disease development, presumably as the result of regulation of cytokine production in inflammatory cells.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, abnormal levels of i subunits were observed in Sjogren's syndrome [49] , inclusion body myositis, myofibrillar myopathy [50] , Crohn's disease [51] and dextran sulfate sodium-induced colitis [52] . These findings suggest a therapeutic benefit from blocking solely the iCP, at least for the above mentioned diseases.…”
Section: S Proteasomes: Validated and Emerging Drug Targetsmentioning
confidence: 99%
“…5,6 Results from my laboratory, as well as other investigators, suggest that these immuno proteasome subunits [low molecular mass polypeptide (LMP) 2 (b1i), multi-catalytic endopeptidase complexlike-1 (b2i), and LMP7 (b5i)] are involved in the pathogenesis of experimental colitis and IBD.…”
Section: Immuno Proteasome Subunits (Lmp2 Lmp7 Lmp10)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In this regard, targeting the LMP7 subunit with a selective small molecule inhibitor (PR-957, ONX-0914) was shown to be effective in a mouse model of UC. 7 To date, the relevant literature seems to suggest that targeting the LMP7 or LMP2 immuno proteasome subunits may be most beneficial for the treatment of IBD.…”
Section: Novel Pharmacological Treatments Targeting the Upsmentioning
confidence: 99%